Synthesis and characterization of two vic-dioximes containing the 1,3-dioxolane ring and 1,4-diaminobutane and their cobalt(II), nickel(II), copper(II) and zinc(II) metal complexes - Canpolat, E; Kaya, M (Kluwer Academic Publ, 2004)
Two new vic-dioxime ligands,(E,E)-N-{4-[(1,4-dioxaspiro[4.4]non-2-ylmethyl)amino]butyl}-N'-hydroxy-2-(hydroxyimino)ethanimidamide ((LH2)-H-1) and (E,E)-N-4-[(1,4-dioxaspiro[4.5]dec-2-ylmethyl)amino]utyl}-N'-hydroxy-2-(hydroxyimino) ethanimidamide ((LH2)-H-2) containing two different heteroatoms (N, O) have been prepared from anti-chloroglyoxime, N-(1,4-dioxaspiro[4.4]non-2-ylmethyl)butane-1,4-diamine ( 3) and N-(1,4-dioxaspiro[4.5]dec-2-ylmethyl)butane-1,4-diamine (4). Co-II, Ni-II and Cu-II complexes of the ligands have a metal: ligand ratio of 1: 2 and the ligands coordinate through the two N atoms, as do most of the vic-dioximes. However, Zn-II complexes of the ligands have a metal: ligand ratio of 1: 1 and the ligands are coordinated only by the N, O atoms of the vic-dioximes. In the Co-II complexes two water molecules, and in the Zn-II complexes a chloride ion and a water molecule, are also coordinated to the metal ion. The structures of the compounds were determined by a combination of elemental analysis, magnetic moments, molar conductances, thermogravimetric analysis (t.g.a.) and spectroscopic (u.v.-vis., i.r., H-1- and C-13-n.m.r.) data.
Keywords: Coordination-Compounds; Mononuclear; Ligands; Ni(Ii); Cu(Ii); Polymers; Linking; Cd(Ii); Zn(Ii)